Dose‐Finding Studies Among Orphan Drugs Approved in the EU: A Retrospective Analysis. (7th September 2018) - Schuller, Yvonne; Gispen‐de Wied, Christine; Hollak, Carla E. M.; Leufkens, Hubertus G. M.; Stoyanova‐Beninska, Violeta
Abstract: In the development process for new drugs, dose‐finding studies are of major importance. Absence of these studies may lead to failed phase 3 trials and delayed marketing authorization. In our study we investigated to what extent dose‐finding studies are performed in the case of orphan drugs for metabolic and oncologic indications. We identified all orphan drugs that were authorized until August 1, 2017. European Public Assessment Reports were used to extract the final dose used in the summary of product characteristics, involvement of healthy volunteers, study type, end points used, number of patients, number of doses, studies in special populations, and dose used for phase 3 studies. Each drug was checked for major objections and dose changes postmarketing. We included 49 orphan drugs, of which 28 were indicated for metabolic disorders and 21 for oncologic indications. Dose‐finding studies were performed in 32 orphan drugs, and studies in healthy volunteers in 26. The absence of dose‐finding studies was mostly due to the rarity of the disease. In this case the dose was determined based on factors such as animal studies or clinical experience. Dose‐related major objections were raised for 9 orphan drugs. Postmarketing dose‐finding studies were conducted in 18 orphan drugs, but dose changes were applied in only 2 drugs. In conclusion, dose‐finding studies in the case of metabolic and oncologic orphan drugs were conducted in the development programs of two thirds of orphan drugs. Dose‐finding studies performed postmarketing suggest that registered doses are not always optimal. It is thus important to perform more robust dose‐finding studies both pre‐ and postmarketing.